Nipple‐sparing mastectomy in patients with BRCA1/2 mutations and variants of uncertain significance. Issue 11 (27th August 2015) - Manning, A. T.; Wood, C.; Eaton, A.; Stempel, M.; Capko, D.; Pusic, A.; Morrow, M.; Sacchini, V.
<x xml:space="preserve">Abstract</x> Background Nipple‐sparing mastectomy (NSM) is associated with improved cosmesis and is being performed increasingly. Its role in BRCA mutation carriers has not been well described. This was a study of the indications for, and outcomes of, NSM in BRCA mutation carriers. Methods BRCA mutation carriers who underwent NSM were identified. Details of patient demographics, surgical procedures, complications, and relevant disease stage and follow‐up were recorded. Results A total of 177 NSMs were performed in 89 BRCA mutation carriers between September 2005 and December 2013. Twenty‐six patients of median age 41 years had NSM for early‐stage breast cancer and a contralateral prophylactic mastectomy. Mean tumour size was 1·4 (range 0·1–3·5) cm. Sixty‐three patients of median age 39 years had prophylactic NSM, eight of whom had an incidental diagnosis of ductal carcinoma in situ. There were no local or regional recurrences in the 26 patients with breast cancer at a median follow‐up of 28 (i.q.r. 15–43) months. There were no newly diagnosed breast cancers in the 63 patients undergoing prophylactic NSM at a median follow‐up of 26 (11–42) months. All patients had immediate breast reconstruction. Five patients (6 per cent) required subsequent excision of the nipple–areola complex for oncological or other reasons. Skin desquamation occurred in 68 (38·4 per cent) of the 177 breasts, and most resolved without intervention. Debridement was required in 13 (7·3 per cent) of the 177 breasts, and tissue‐expander or implant removal was necessary in six instances (3·4 per cent). Conclusion NSM is an acceptable choice for patients with BRCA mutations, with no evidence of compromise to oncological safety at short‐term follow‐up. Complication rates were acceptable, and subsequent excision of the nipple–areola complex was rarely required.